FORT FOUNDATION IN MADRASAH MULTICULTURAL EDUCATION TO DISPEL RADICAL RIGHT - Hendrawan, Kresna (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Islam is a religion rahmatan lil Alamin mercy to all the worlds, Islam is a peacefulreligion, and Islam recognizes the multicultural to assume that all human beings areequal, human glory of Islam measure levels of devotion to god. Islam highly appreciatethe difference, but in practice often arise precisely the opposite tendency, with morehighlight each class differences with one another. Identity Islam and views betweengroups are often made in the interests of the strategic for the group of people to satisfy hisdesire, This situation is exacerbated by the proliferation of radicalism Islam who crave theglory of Islam by claiming that his group is the most true to the principle of radicalism isthe best way to achieve greatness of Islam , this is a great danger that could divide thenation. Islamic radicalism appears like a fungus in the rainy season, Islamic radicalismdiIndonesia appear bright latently or openly. The radical right with the attitude ofintolerance, bigotry, always felt completely alone and assume people / other religionsfalse, exclusive, revolutionary attitude, tend to use violent means to achieve its objectivesand attitude to understand religious texts textually of partial and ignores the value -thevalue of Islamic modernity. Madrasah schools in particular is one of the strategic placesto spread the teachings of the radical right, because young people are deciding the futureof the nation. Multicultural education at the school is very necessary, because the madrasastudents should realize that they are in a heterogeneous culture although he memempuheducation in state schools tend to have a homogenous culture. This study uses literaturestudy. The results Showed that the multicultural education in madrassas have some: (1)the importance of education in Madrasah multikural (2) the danger of right-wing radicals(3) the practice of multicultural education in MadrasahKeywords: Multicultural, Radical Right.